The effect of adding nano-SiO2 and nano-Al2O3 on properties of high calcium fly ash geopolymer cured at ambient temperature - Phoo-ngernkham, Tanakorn; Chindaprasirt, Prinya; Sata, Vanchai; Hanjitsuwan, Sakonwan; Hatanaka, Shigemitsu (Materials & Design, 2014)
•Use of nano-SiO2 and nano-Al2O3 as additive enhanced geopolymer property.•Strength increased due to formation of additional CSH/CASH and NASH gel.•Hydration products formed and filled pore to make dense and strong geopolymer. This article presents the effect of adding nano-SiO2 and nano-Al2O3 on the properties of high calcium fly ash geopolymer pastes. Nano-particles were added to fly ash at the dosages of 0%, 1%, 2%, and 3% by weight. The sodium hydroxide concentration of 10 molars, sodium silicate to sodium hydroxide weight ratio of 2.0, the alkaline liquid/binder ratio of 0.60 and curing at ambient temperature of 23°C were used in all mixtures. The results showed that the use of nano-SiO2 as additive to fly ash results in the decrease of the setting time, while the addition of nano-Al2O3 results in only a slight reduction in setting time. Adding 1–2% nano-particles could improve compressive strength, flexural strength, and elastic modulus of pastes due to the formation of additional calcium silicate hydrate (CSH) or calcium aluminosilicate hydrate (CASH) and sodium aluminosilicate hydrate (NASH) or geopolymer gel in geopolymer matrix. In addition, the additions of both nano-SiO2 and nano-Al2O3 enhances the shear bond strength between concrete substrate and geopolymer.